2017
DOI: 10.1016/s1470-2045(17)30421-7
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab versus standard, single-agent therapy of investigator's choice in recurrent or metastatic squamous cell carcinoma of the head and neck (CheckMate 141): health-related quality-of-life results from a randomised, phase 3 trial

Abstract: Bristol-Myers Squibb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
261
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(273 citation statements)
references
References 42 publications
11
261
0
1
Order By: Relevance
“…At least five antibodies have been studied in the clinical trials, leading to the approval of five different checkpoint inhibitors. Although higher PD‐L1 expression tends to correlate with a greater objective response to checkpoint blockade, survival benefit is seen regardless of PD‐L1 expression across other tumor types (melanoma, urothelial carcinoma, head and neck squamous cell carcinoma, Merkel cell carcinoma, and renal cell carcinoma) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least five antibodies have been studied in the clinical trials, leading to the approval of five different checkpoint inhibitors. Although higher PD‐L1 expression tends to correlate with a greater objective response to checkpoint blockade, survival benefit is seen regardless of PD‐L1 expression across other tumor types (melanoma, urothelial carcinoma, head and neck squamous cell carcinoma, Merkel cell carcinoma, and renal cell carcinoma) .…”
Section: Discussionmentioning
confidence: 99%
“…Except for pembrolizumab for non‐small cell lung cancer and gastric and GEJ adenocarcinoma, FDA approvals of immune checkpoint inhibitors have not required companion PD‐L1 testing. Moreover, the clinical trials leading to approval used different PD‐L1 antibodies for IHC testing with different staining thresholds in cancer and immune cells across different cancer types (Table ) . Thus, PD‐L1 testing is complex and inconsistent, with different implications for clinical use depending on tumor type.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of HRQoL from the phase 3 K EYNOTE-045 study showed that pembrolizumab improved HRQoL when compared with chemotherapy in patients with platinum-refractory advanced UC [161]. Several phase 3 studies comparing nivolumab with chemotherapy reported similar findings in treatment-naïve patients with melanoma (CheckMate 066) [162] and in patients with recurrent HNSCC (CheckMate 141) [31,163]. Nivolumab was also associated with HRQoL improvement over the targeted agent, everolimus, in previously treated patients with advanced RCC (CheckMate 025) [164].…”
Section: Quality Of Life Associated With Icbsmentioning
confidence: 97%
“…Most common AEs were fatigue (14.0%), nausea (8.5%) and rash (7.6%); the most common grade 3 or 4 events were fatigue (2.1%) and anemia (1.3%). Furthermore, an exploratory analysis proved that nivolumab was superior in terms of health-related quality of life 24. This trial has led to the FDA approval of nivolumab in November 2016 for the treatment of patients with R/M HNSCC with disease progression on, or after, a platinum-based therapy.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%